Understanding the Socioeconomic Differences of Urban and Camp-Based Refugees in Kenya : Comparative Analysis Brief - 2018 Kalobeyei Settlement, 2019 Kakuma Camp, and 2020-21 Urban Socioeconomic Surveys - World Bank; United Nations Refugee Agency (UNHCR) (World Bank, Washington, DC, 2022)
The comparative analysis on the socioeconomic conditions of urban and camp-based refugees in Kenya builds upon the findings of the Kalobeyei, Kakuma and Urban Socioeconomic Surveys (SES). It offers an analytical understanding about key differences between refugees while providing explanations, and policy recommendations.